Comparing the Efficacy of Ketogenic Diet with Low-Fat Diet for Weight Loss in Obesity Patients: Evidenc-Based Case Report - Nurul Ratna Manikam; Nico I Pantoro; Karina Komala; Ayu Diandra Sari (Indonesian Nutrition Association, 2018)
Introduction Obesity is a nutritional disease which is still a health burden particularly in Jakarta. The main treatment for obesity is nutritional intervention. Nowadays, several dietary approaches have been developed, including ketogenic diet, which is still controversial. Methods Literature search had been done within 4 databases including PubMed®, Cochrane®, Google® Scholar, and Science Direct®, using keywords: obesity, ketogenic diet, low-fat diet, and weight loss. Then, Medical Sub Heading (MeSH) was used. The search resulted in two articles which were appraised according to aspects of validity, importance, and applicability Results A randomized-controlled trial study showed similar effect of weight loss with ketogenic diet compared to low-fat diet. On the other hand, a meta-analysis study showed ketogenic diet caused more weight loss than low-fat diet. Both studies showed an increased risk of cardiovascular disease from the ketogenic diet group, which were shown by a decrease of flow-mediated dilatation and an increase of LDL-C. Conclusion Ketogenic diet shows a better long-term effect for weight loss in obese patients than low-fat diet. However, ketogenic diet may increase the cardiovascular event risk significantly.